1+1-1+1-1+1-1+1-1+1+1-2
Răspunsuri la întrebare
Răspuns de
3
1 + 1 - 1 + 1 - 1 + 1 - 1 + 1 - 1 + 1 + 1 - 2 =
2 - 1 + 1 - 1 + 1 - 1 + 1 - 1 + 1 + 1 - 2 =
1 + 1 - 1 + 1 - 1 + 1 - 1 + 1 + 1 - 2 =
2 - 1 + 1 - 1 + 1 - 1 + 1 + 1 - 2 =
1 + 1 - 1 + 1 - 1 + 1 + 1 - 2 =
2 - 1 + 1 - 1 + 1 + 1 - 2 =
1 + 1 - 1 + 1 + 1 - 2 =
2 - 1 + 1 + 1 - 2 =
1 + 1 + 1 - 2 =
2 + 1 - 2 =
3 - 2 = 1
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă